Heart Valve Abnormalities in Systemic Sclerosis Patients: A Multicenter Cohort Study and Review of the Literature. Issue 1 (January 2022) - Colaci, Michele; Schinocca, Claudia; Bosco, Ylenia Dal; Ronsivalle, Giuseppe; Guggino, Giuliana; de Andres, Ilenia; Russo, Alessandra A.; Sambataro, Domenico; Sambataro, Gianluca; Malatino, Lorenzo
Abstract : Background: Systemic sclerosis (SSc) is a chronic autoimmune disease that is characterized by vasculopathy and fibrosis of the skin and visceral organs. Heart valve diseases are poorly described and generally not considered typical of SSc. We aimed to describe valvular abnormalities in a multicenter cohort of SSc patients and to investigate their correlation with SSc features. Methods: We recruited 118 consecutive SSc patients (male/female, 14/104; mean age, 55.2 ± 12.1 years) in 3 rheumatology centers in Sicily, Italy, from January to October 2019. Results: Mitral and tricuspid valve insufficiency was found in 85% and 91% of patients, respectively; regurgitations were generally mild and never severe. Mitral stenosis was rare (2%), and tricuspid stenosis was not observed. Sclerosis and calcification were present in 30% of mitral valves and in only 4% of tricuspid valves. The aortic valve was affected in 25% of cases, and it generally presented as regurgitation or sclerosis, whereas stenosis was rare (3%). Finally, 11% of SSc patients showed regurgitation of the pulmonary valve. No specific associations between SSc features and valve alterations were found. Conclusions: Valvular diseases are frequently observed in SSc patients, with a predominant pattern of valvular regurgitations. Therefore, echocardiography should be routinely performed during SSc patient follow-up, considering the potential influence of additional cardiac involvement in the prognosis of these patients.